The use of elderberry juice in the production of marmalade - Tsira Khutsidze; Eliza Pruidze (Theoretical Hypotheses and Empirical Results, 2025)
widely spread in Georgia, in the production of marmalade to expand the assortment and improve its nutritional value. Its berries are rich in vitamins, macro- and micro-elements, polyphenols, pectin, coloring, and other biologically active substances. The marmalade product prepared using black elderberry juice, with their organoleptic and physicochemical indicators, fully comply with the values specified in the standard. The plastic strength index of the developed product is within normal limits, compared to the control sample, and its storage duration has increased from 60 days to 70 days, which was confirmed by microbiological tests. This can be explained by the bactericidal and antimicrobial action of elderberry, as well as by the rather high content of substances with antioxidant action. The microbiological indicators of the developed product indicate their sanitary safety. By reducing the amount of sugar in the recipe of the developed product by 14.9%, the caloric content of the products was reduced by 50 kcal, or 15.3%, compared to the control sample without worsening the organoleptic indicators. Due to the use of gelatin as a jellifying agent, the biological value of the products increased.